DDT resistance in three local populations of rice weevils - Santos, Flora L.; Lim-Sylianco, Clara Y. (1985)
The relationship between DDT resistance and dehydrochlorination of DDT by three local populations of rice weevils was studied. In-vitro studies showed that DDE formation increased with increasing resistance to DDT. Variation in the amount of DDE fromed from a fixed dose of DDT was also observed in the presence of several modifier compounds. Treatment with phenobarbital could activate as well as inhibit the transformations of DDT to DDE in the rice weevils tested. The most pronounced effect on DDT dehydrochlorinase activity was the activation of the enzyme in both the A and the F strains of rice weevils exposed for 22 hours to the DDT-phenobarbital mixture. Inhibition by phenobarbital was alos observed in weevils pretreated for 24 hours with the modifier compound. Piperonyl butoxide and carbaryl exerted predominantly inhibitory effects on DDT dehydrochlorinase although a slight increase in enzyme activity was detected in weevils with piperonyl butoxide 24 hours before DDT application. At 18 hours treatment with DDT-modifier compound mixture, only small changes in DDT dehydrochlorinase activity were obtained. At 27 hours treatment with the modifier compounds, the inhibitory effects of piperonyl butoxide and of carbaryl were still observed. In phenobarbital-treated weevils, however, enzyme activity had returned to normal levels.
This Article/Publication is available upon request to NAST/the Author Address: 3rd Level Philippine Science Heritage Center DOST Complex, Bicutan, Taguig, 1631 Metro Manila Direct Lines: (632) 838-77-39/66/92 Trunklines: (632) 837- 2071 to 82 ext. 2170-75 FAX No.: (632) 837-3170 E-mail: secretariat@nast.ph
Includes bibliographical references (page 157) and index.
Keywords: Agriculture; Rice weevils -- Pesticide resistance